Towards ultrafast dynamics with split-pulse X-ray photon correlation spectroscopy at free electron laser sources - W. Roseker; S. O. Hruszkewycz; F. Lehmkühler; M. Walther; H. Schulte-Schrepping; S. Lee; T. Osaka; L. Strüder; R. Hartmann; M. Sikorski; S. Song; A. Robert; et al. (Nature Communications, 2018)
X-ray photon correlation spectroscopy has been mainly used to measure slow dynamics using synchrotron sources. Here the authors demonstrate the split-and- delay pulse set-up to study nanosecond dynamics of gold nanoparticles using XPCS with free electron laser pulses.